Gravel Deposits Of Dauki-Piyain River Bed And Surrounding Flood Plains: A Case Study (Journal of the Asiatic Society of Bangladesh, Science, 2015)
The Dauki-Piyain river is the major source of gravels in Jaflong area which is located on the alluvial plain south of the Khasi-Jainta Hills. Jaflong gravels comprise quartzite, granite, gneiss, amphibolite, basalt, sandstone and conglomerate. The gravels are mostly fresh and hard and can be used as good construction materials. The deposition of gravels is controlled by the frequency and intensity of water-flow in the Dauki-Piyain river forming the Jaflong quarry. The Dauki river is constantly changing its course. Controlling the river course and keeping its tract clear from debris will make the replenishment of the gravel deposit steady. The main economic activities of the local people are mostly dependent on the gravel and sand extraction business from Jaflong quarry. It is found that about 30,00,000 cubic meters of gravel from 200 hectares areas are extracted per year from the Dauki-Piyain river of Jaflong. The average revenue collected by the Government of the People’s Republic of Bangladesh from this location stands at approximately 30.00 million taka per year.Asiat. Soc. Bangladesh, Sci. 41(2): 225-232, December 2015